Transforming Women's Leadership in Improving Service Quality in Islamic Boarding Schools - Muhammad Ainul Yaqin; I'if Hafidatuz Sholihah (Managere: Indonesian Journal of Educational Management, 2025)
This research aims to analyze the transformation of women's leadership in improving service quality in the Islamic boarding school environment. Women's leadership in Islamic boarding schools still faces various challenges, both from cultural, structural and policy aspects. Therefore, this research seeks to reveal how women's leadership experiences transformation and contributes to improving the quality of educational services in Islamic boarding schools. This research uses a qualitative approach with a case study method at the Nurul Jadid Islamic Boarding School. Data was collected through observation, in-depth interviews with women leaders, teaching staff, and students, as well as analysis of relevant documents. Data analysis was carried out using content analysis, discourse analysis and interpretative analysis to understand women's leadership patterns and their impact on improving the quality of services in Islamic boarding schools. The research results show that women's leadership at the Nurul Jadid Islamic Boarding School has experienced a significant transformation, marked by increased women's participation in strategic decision making as well as the application of empathy-based, collaborative and innovative leadership approaches. The main factors that support this transformation are increasingly inclusive Islamic boarding school policies, increasing the competence of female leaders, as well as support from various parties, including students and teaching staff. However, cultural barriers and gender stereotypes remain challenges that need to be overcome. The implication of this research is the need to strengthen policies that better support women's leadership in Islamic boarding schools, as well as developing training and mentoring programs for prospective women leaders. In this way, women's leadership can further contribute to improving the quality of educational services and creating a more professional, inclusive and sustainable Islamic boarding school management system.